School based screening tools for childhood obesity: a comparison of TSFT, WHR and BMI - Mukhopadhyay, Sujaya; Bhattacharjee, Prasun; Joshi, Payas (International Journal of Contemporary Pediatrics, 2017)
Background: Obesity is an emerging health problem in children and adolescents. Various screening tools are there for assessment of nutritional status and this study was done to compare various methods to screen for obesity and overweight in adolescents that can be used during school health check-up. Methods: This study was conducted in the urban schools of Vadodara city. 609 students were included in the study. Results: Maximum students were in the age group of 16-18 year of which 57.9% were males and 42.03 % females. By using BMI, 4.1% students were found to be obese and 12.8% overweight. 10% students had WHR above the cut-off levels. In 11.3% TSFT was above 90th centile. Conclusions: Comparison between the three parameters done using ANNOVA, shows that TSFT is better than BMI in detecting Obesity.